MDP-99mTc Biodistribution Alteration on a Bone Scan after Pamidronate Therapy: Case Report - Mello, Maria Eduarda (2010)
Disodium pamidronate therapy is often instituted for the treatment of various conditions, such as oncogenic hypercalcemia, osteoporosis and Paget’s disease, and could interfere in the biodistribution of MDP-99mTc on bone scan. The authors report a case of important decrease of bone uptake and increase of soft tissues and lungs uptake in a neoplastic patient presenting oncogenic hypercalcemia, who had just been treated with intravenous pamidronate. The more likely mechanism to be responsible for these alterations is the competition of MDP for the same binding site as the pamidronate in hydroxiapatite crystals. Increased lung uptake probably resulted from microcalcifications caused by hypercalcemia presented by the patient. Nuclear medicine physicians should, therefore, be aware of this potential pitfall in order to avoid misdiagnosis.